Penerapan Teknik Skrambel Pada Pelajaran Bahasa Indoensia Kelas 3 SD N 1 Munggung Karangdowo Klaten - Khuriyati, Tutik (Universitas Sebelas Maret, 2022)
Basically, the Merdeka Curriculum is based on the concept of independent learning using project-based learning, essential and differentiated learning. To achieve the concept of independent learning, there are several variations of learning techniques that can attract students' attention. Learning techniques that have a large role in learning will produce good results for students. One learning technique is the scrembel technique, this technique can increase students' concentration and speed of thinking. This technique encourages students to find answers and solutions to existing problems. This research aims to determine the scrembel technique in Class 3 Indonesian language lessons at SD N 1 Munggung. The research subjects were teachers and class III students at SDN 1 Mungung, totaling 30 students. The research object studied was improving learning outcomes in reading comprehension using the scrambling technique in class III students at SDN 1 Munggung.